1994
DOI: 10.1099/13500872-140-2-341
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory circuits involved with pH-regulated gene expression in Salmonella typhimurium

Abstract: Salmonella typhimurium encounters a variety of acid conditions during both its natural and pathogenic existence. The ability of this organism t o respond transcriptionally to low pH is an area of active interest but little knowledge. As part of an ongoing investigation of low-pH adaptation, 18 pH-controlled IacZ operon fusions in Salmonella typhimurium have been identified (15 in this study) and categorized into a t least 11 different loci. They include iroA (at 57 min), aciA (99 min), aciB (90-93 min), aciD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 42 publications
3
53
0
Order By: Relevance
“…Further evidence for this is found in Table 2, which illustrates the effects of loss-offunction fur (fur-2), superrepressor fur (fur s -15), and iron-blind fur-9 mutations on the expression of a hyd-lacZ fusion. We have previously shown that the hyd locus is coinduced by acid and anaerobiosis and that Fur is required for hyd induction at pH 5.8 (19). This finding is confirmed in Table 2 (JF2392).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Further evidence for this is found in Table 2, which illustrates the effects of loss-offunction fur (fur-2), superrepressor fur (fur s -15), and iron-blind fur-9 mutations on the expression of a hyd-lacZ fusion. We have previously shown that the hyd locus is coinduced by acid and anaerobiosis and that Fur is required for hyd induction at pH 5.8 (19). This finding is confirmed in Table 2 (JF2392).…”
supporting
confidence: 80%
“…This conclusion is based on the ability of the H90R Fur mutant to mediate acid induction of specific Fur-dependent ASPs and enable induction of acid tolerance in spite of the fact that the mutant Fur cannot mediate iron regulation. We have also provided evidence that Fur can, either directly or indirectly, act as a positive regulator of the pH-regulated locus, hyd (19). This acid control also appears to be iron independent in that a Fur superrepressor and the iron-blind Fur H90R still regulated hyd in response to pH.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Here we identify the gene coding for the E. coli arginine-agmatine exchanger used in XAR, a membrane protein spanning 12 amino acids of unknown function, designated yjdE (b4115) and now named adiC by us and, recently, by others (12). The adiC gene is a homologue of a gene, aniC, in Salmonella enterica serovar Typhimurium that is conjectured to be the possible arginine-agmatine exchanger in arginine XAR (25) and was previously identified from a genetic analysis by using lacZ transcriptional fusion proteins activated under conditions of low pH (10). We show that adiC functions specifically in arginine XAR and that the dependence of transport activity on arginine concentration and pH naturally accounts for its role in maintaining cell viability under strong acid stress conditions.…”
mentioning
confidence: 99%
“…At least six regulatory classes of nutrient, starvation-inducible loci have been characterised for the salmonellae [7]. To assign biological significance to any putative character or virulence determinant, it is necessary to demonstrate its expression and sometimes its extracellular release in relation to host environmental cues or in appropriate ecological settings.…”
Section: Introductionmentioning
confidence: 99%